PERAN ICE BREAKING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SEKOLAH DASAR - Sa’adah, Nelly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning motivation is an important factor in realizing the success of learning. The use of media or methods in learning is also important in fostering student learning motivation. This study aims to analyze the role of ice breaking in increasing the learning motivation of grade II elementary school students. The research method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. The results of the study indicate that the application of ice breaking gets a good response from students and can effectively increase students' attention, enthusiasm and occupation in learning. The ice breaking activities used are varied and relevant to the circumstances or needs of students in learning, helping to create a more active and less boring learning environment.   Keywords: ice breaking, learning motivation, elementary education